Self‐expanding metal stents for acute refractory esophageal variceal bleeding: A systematic review and meta‐analysis. Issue 5 (22nd April 2016) - McCarty, Thomas R; Njei, Basile
Abstract : Background and Aim: Esophageal variceal bleeding is a severe complication of portal hypertension with significant morbidity and mortality. A substantial portion of cirrhotics fail to respond to conventional medical therapy and band ligation, necessitating alternative treatments including self‐expanding metal stent (SEMS) placement for acute refractory esophageal variceal bleeding. In the present study, we carried out a systematic review and structured meta‐analysis of all eligible studies to evaluate the technical feasibility, safety, clinical efficacy, and survival advantage of SEMS placement for the treatment of of acute esophageal variceal bleeding. Methods: Searches of PubMed, EMBASE, Web of Science, and the Cochrane Library databases were carried out through December 2015. Individual study proportions were transformed into a quantity using the Freeman–Tukey variant of the arcsine square root transformed proportion. Combined weighted proportions, and meta‐regression were then determined. Results: The search yielded 12 studies involving n = 155 patients included in our meta‐analysis. Pooled clinical success rate in achieving hemostasis within 24 h was 96% (95% CI, 0.90–1.00). Technical success for SEMS deployment endoscopically was achieved in 97% of patients (95% CI, 0.91–1.00). Total adverse events (including rebleeding after 48 h, ulceration, and stent migration) were shown in 36% of patients after SEMS placement (95% CI, 0.23–0.50). Pooled 30‐day and 60‐day survival rates were 68% (95% CI, 0.56–0.80) and 64% (95% CI, 0.48–0.78), respectively. Conclusion: This study demonstrated that esophageal SEMS placement is a technically feasible modality and highly efficacious in achieving hemostasis in acute esophageal variceal hemorrhage.